2021
DOI: 10.1513/annalsats.202006-696fr
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Daytime Sleepiness in Obstructive Sleep Apnea. Mechanisms and Clinical Management

Abstract: Many patients with obstructive sleep apnea (OSA) experience excessive daytime sleepiness (EDS), which can negatively affect daily functioning, cognition, mood, and other aspects of well-being. Although EDS can be reduced with primary OSA treatment, such as continuous positive airway pressure (CPAP) therapy, a significant proportion of patients continue to experience EDS despite receiving optimized therapy for OSA. This article reviews the pathophysiology and clinical evaluation and management of EDS in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(57 citation statements)
references
References 86 publications
0
44
0
1
Order By: Relevance
“…Hippocampus damage caused by OSA may lead to worsening daytime sleepiness as well as cognitive impairments. 46 The present study has several limitations. The DTI data had a limited number of isotropic gradient directions (n = 15) and were measured at a relatively low diffusion weight (b = 1000 s/mm 2 ).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Hippocampus damage caused by OSA may lead to worsening daytime sleepiness as well as cognitive impairments. 46 The present study has several limitations. The DTI data had a limited number of isotropic gradient directions (n = 15) and were measured at a relatively low diffusion weight (b = 1000 s/mm 2 ).…”
Section: Discussionmentioning
confidence: 83%
“…Hippocampus damage caused by OSA may lead to worsening daytime sleepiness as well as cognitive impairments. 46 …”
Section: Discussionmentioning
confidence: 99%
“…Around 25–50% of patients with OSA will experience EDS, and it can negatively affect daily functioning, cognition, mood, and other aspects of well-being [ 22 ]. Its pathophysiology involves chronic intermittent hypoxia and sleep fragmentation causing oxidative injury and changes in neurons and neurotransmitters that regulate wake-promoting regions of the brain [ 23 ]. Such is the link between EDS and OSA that in our study we found a weak positive correlation between STOP-Bang and ESS scores, and a statistically significant association between OSA risk and daytime sleepiness categories.…”
Section: Discussionmentioning
confidence: 99%
“…Among those who do report EDS, studies have shown that the severity of EDS does not correlate with the severity of OSA (as determined by apnea hypopnea index [AHI]), suggesting that factors other than respiratory events and arousal (eg, hypoxia-and/or sleep fragmentation-related brain injury [8]) contribute to EDS in this population [9][10][11]. Indeed, EDS has been shown to persist in some patients despite the normalization of breathing, oxygenation, and sleep quality with continuous positive airway pressure (CPAP) (the gold standard treatment for OSA), known as residual EDS [12,13].…”
Section: Prevalence Of Excessive Daytime Sleepiness In Obstructive Sleep Apneamentioning
confidence: 99%